Carbon Nitride as a Ligand: Selective Hydrogenation of Terminal Alkenes Using [(η5‐C5Me5)IrCl(g‐C3N4‐κ2N, N')]Cl. Issue 30 (30th April 2020) - Coulson, Ben; Lari, Leonardo; Isaacs, Mark; Raines, Daniel J.; Douthwaite, Richard E.; Duhme‐Klair, Anne‐K.
Abstract: Anchoring a homogeneous catalyst onto a heterogeneous support facilitates separation of the product from the catalyst, and catalyst‐substrate interactions can also modify reactivity. Herein we describe the synthesis of composite materials comprising carbon nitride (g‐C3 N4 ) as the heterogeneous support and the well‐established homogeneous catalyst moiety [Cp*IrCl] + (where Cp*=η 5 ‐C5 Me5 ), commonly used for catalytic hydrogenation. Coordination of [Cp*IrCl] + to g‐C3 N4 occurs directly at exposed edge sites with a κ 2 N, N' binding motif, leading to a primary inner coordination sphere analogous to known homogeneous complexes of the general class [Cp*IrCl(NN‐κ 2 N, N' )] + (where N, N' =a bidentate nitrogen ligand). Hydrogenation of unsaturated substrates using the composite catalyst is selective for terminal alkenes, which is attributed to the restricted steric environment of the outer coordination sphere at the edge‐sites of g‐C3 N4 . Abstract : Bulky solid ligand : Selective catalytic hydrogenation of terminal alkenes is observed when [Cp*IrCl] + is supported on g‐C3 N4 . Direct coordination of [Cp*IrCl] + to g‐C3 N4 occurs via κ 2 N, N ' binding and is limited to exposed edge sites. The restricted steric environment at the Ir atom results in slow but highly selective catalysis.